Analisis Tingkat Kepuasan dalam Penerapan PPDB Online SMKN Kota Palembang - Mardiana, Mardiana (Teknomatika, 2016)
PPDB web-based used as a service base and always be improved, so it is expected to provide convenience for students and parents also for the community in registering. In the application, PPDB Online is still poorly understood for candidate students due to the complicated registration system process and the lack of knowledge in IT for candidate students who wish to enroll. Problems arising from concerns about the difficulty of registering, so that Dinas Pendidikan of Palembang City in collaboration with the SMP / SMA / SMKN to make various efforts to minimize such concerns. This study aims to determine the level of satisfaction of students in the application of PPDB Online system SMKN in Palembang School Year 2015-2016. The population of this study was taken from students SMKN Palembang city. Research respondents were determined using Simple Random Sampling technique. This research uses EUCS Model (End User Computing Satisfaction) consisting of Content, Accuracy, Format, Ease, Timeliness, and Satisfaction. The result of this research is satisfaction variable which is the level of user satisfaction that is t value = -0,407> t table = 0,678 this means the lack of user satisfaction level when the application of PPDB Online by new students. Â Keywords-PPDB, EUCS, SPSS.